Foreign Direct Investment in Mexico since the Approval of NAFTA - Cuevas, Alfredo; Messmacher, Miguel; Werner, Alejandro (Published by Oxford University Press on behalf of the World Bank, 2014)
Cross-country panel data are used to assess the effect of free-trade agreements on flows of Foreign Direct Investment (FDI). Free-trade agreements are found to have a significant positive effect on FDI flows, and free-trade agreements are found to matter more for the smaller members of the agreement. For example, the North American Free-Trade Agreement's (NAFTA) effect on FDI flows into Mexico is much larger than its effect on flows into the United States. These cross country results are used to assess NAFTA's effect on FDI flows into Mexico. After controlling for a set of other factors such as an increase in worldwide FDI flows the trade agreement is found to generate FDI flows nearly 60 percent higher than they would have been without the agreement.